Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Guru pada SDN Gugus 2 Kelurahan Harapan Jaya - Anisa Anisa; Bintang Narpati (Departement of Mathematics Education, 2023)
Finding out how much leadership style and work discipline affect teacher performance at SDN Gugus 2 Harapan Jaya Village was the goal of this study. In this study, all of the participants were instructors in cluster 2. This research employed a quantitative approach. 80 respondents were given questionnaires to complete in order to collect data. The sampling strategy for this investigation used the non-probability sampling method. The study's findings show that leadership style and work discipline are partially significant variables, with the calculated t value being higher than the t table and variables. The estimated F value is more than the F table with a significant value of less than 0.05, according to the findings of the simultaneous F test. The conclusion is that either H0 is rejected or H is accepted, indicating that both leadership style and work discipline have a big impact on teacher performance.”